Phylogenetic Analysis of Schistosoma japonicum Based on 16S rRNA Gene - Safani Safani; Sutrisnawati Sutrisnawati; Manap Trianto; I Nengah Kundera; Zulaikhah Dwi Jayanti; Masrianih Masrianih (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Schistosomiasis is a neglected tropical disease caused by trematode worms of the genus Schistosoma and remains a public health concern in several endemic areas of Central Sulawesi, Indonesia. DNA-based molecular approaches have been increasingly applied to support species identification and the analysis of genetic relationships in Schistosoma japonicum. This study aimed to investigate the phylogenetic relationships and genetic variation of S. japonicum based on the mitochondrial 16S rRNA gene. Samples of Oncomelania hupensis lindoensis were collected from endemic areas surrounding Lake Lindu, Central Sulawesi, Indonesia. Detection of S. japonicum was performed using the crushing method, followed by DNA extraction with the GS 100gSYNCTM DNA Extraction Kit. Amplification of the 16S rRNA gene was carried out using the Polymerase Chain Reaction (PCR) technique with the primers LR13107-F and LR12647-R. Sequence data were analyzed using BLAST, MEGA 11, MESQUITE, DNASTAR, GeneStudio, and DnaSP software. Phylogenetic trees were reconstructed using the Neighbor-Joining (NJ) and Maximum Likelihood (ML) methods with 10,000 bootstrap replicates. PCR amplification produced clear and high-quality DNA bands. BLAST analysis revealed query cover values ranging from 99.90% to 100% and sequence identity of 100% with Schistosoma japonicum sequences available in GenBank. Genetic variation analysis indicated low genetic diversity, characterized by two haplotypes, one variable site, haplotype diversity of 0.500 ± 0.170, and nucleotide diversity of 0.00055 ± 0.00015. Nucleotide composition analysis showed that thymine (T) was the most abundant nucleotide (43.53%), and the A+T content (72.14%) was higher than the G+C content (27.87%), a characteristic feature of mitochondrial genomes. Phylogenetic reconstruction using both NJ and ML methods consistently clustered the Central Sulawesi samples with S. japonicum populations from Shanghai and Guangdong, China, with strong bootstrap support values ranging from 99% to 100%. Genetic distance analysis based on the Kimura 2-Parameter model revealed genetic divergence values of 0.00–0.00% among Central Sulawesi samples and between the Indonesian and Chinese populations, indicating very close genetic relationships and high genetic homogeneity. These findings demonstrate that S. japonicum populations in Central Sulawesi exhibit low genetic variation and share close phylogenetic relationships with other Asian populations, providing valuable molecular information to support the development of schistosomiasis surveillance and control strategies in Indonesia.